Negotiating Multiculturalism in Rural Indonesia: The Structural-Functional Role of Muslim Community Leaders in Social Cohesion - Siti Anur Rambe; Efi Brata Madya (Assyfa Journal of Islamic Studies, 2026)
This study explores the structural-functional role of Muslim community leaders in fostering social cohesion within a multicultural rural context in Tanjung Medan Village, Bilah Barat District, Labuhanbatu Regency. While cultural, linguistic, and ethnic diversity often presents structural friction in rural Indonesian communities, social harmony remains intact through active local leadership. Utilizing a qualitative descriptive approach, data were gathered through observations, in-depth interviews, and document analysis involving Muslim community leaders, traditional figures, and village administrators. The findings demonstrate that Muslim community leaders perform essential integrative functions to maintain social equilibrium through proactive strategies, including joint social initiatives, rural infrastructure development, inclusive religious and mutual-aid association (Serikat Tolong Menolong/STM) activities, and deliberative consensus-building (musyawarah). Furthermore, these leaders fulfill structural roles as mediators, advisors, and social catalysts in embedding tolerance and collective solidarity. Despite potential constraints stemming from divergent customs, language, and ethnicity, peaceful coexistence is sustained via effective communication, mutual respect, and cross-group cooperation. In conclusion, Muslim community leaders serve as pivotal structural-functional anchors in negotiating multiculturalism and sustaining a harmoniously integrated, peaceable rural society.